Perancangan dan Pembuatan Sistem Informasi Penjualan Pada Restoran Pondok Jimbaran - Edy Budi Harjono Sibarani (PT. ALHAFI BERKAH INDONESIA, 2023)
A Pondok Jimbaran restaurant is a business in the culinary field where the sales information system is still run manually. As in the case of data collection, ordering and making reports, everything is written in a small book and stored in a ledger. The purpose of this research is to design an application that can simplify everything related to restaurant sales. The research method used is a survey method which is included in the quantitative research method that uses data collection techniques by conducting interviews and using the waterfall method as system development steps. The result of this research is an application of a computerized sales information system to make it easier for workers to carry out their work.